Efficacy of 2% metronidazole gel in moderate acne vulgaris - Effat Khodaeiani; Rohollah F Fouladi; Neda Yousefi; Mehdi Amirnia; Shahla Babaeinejad; Javad Shokri (Wolters Kluwer Medknow Publications, 2012)
Background: Acne vulgaris is an inflammatory disease of the pilosebaceous units. Various systemic and topical options are available for its treatment. Aims: This study aimed to evaluate the efficacy of 2% metronidazole gel in acne vulgaris. Materials and Methods: Double-blind, randomized, placebo-controlled, split-face clinical trial. Seventy young adults with moderate acne vulgaris received 2% metronidazole gel on the right side of their face and placebo on the left side of their face twice daily for 8 weeks. The number of inflamed and noninflamed facial lesions and side effects of treatment were documented on weeks 1, 2, 4, and 8. The patients' overall satisfaction was recorded at the end of the study. For statistical analysis we used the repeated-measures analysis, the chi-square test, Fisher's exact test, and the independent-samples t-test as appropriate. Results: Counts of inflamed and noninflamed facial lesions were comparable between the two sides at baseline. The number of the lesions was significantly lower on the metronidazole-treated side at all follow-up visits. Erythema and oily face decreased by 85.7% and 87.1%, respectively, on the metronidazole-treated side. Mild burning sensation and dryness on the metronidazole-treated side was reported by 3.4% and 22.9% of the patients, respectively. Eighty-eight percent of the patients were satisfied with the results of treatment on the metronidazole-treated side. Conclusions: Metronidazole gel (2%) is an effective, safe, and well-tolerated topical medication for moderate acne vulgaris.